PUBLIC SPEAKING LEADERSHIP UNTUK MENINGKATKAN MOTIVASI KINERJA PEGAWAI DI HOTEL SANTIKA PREMIERE PADANG - Ghufran Maulana Abdillah (LPPM Universitas Ekasakti, 2023)
Public speaking is a person's ability to speak in public correctly so that the message can be clearly conveyed and the purpose of speaking can be directly obtained. Public Speaking is very important to support the realization of the goals of the management itself, one of which is to improve the knowledge and skills of hotel employees. Of the various non-technical skills or competencies required by tourism industry human resources, effective communication competencies both orally and in writing are non-technical skills with a very large role. For example, the style of language in communicating with employees is important in increasing employee motivation and also company performance. In this study, the authors examine the effect of public speaking and communication styles that occur at Hotel Santika Premiere Padang on the work motivation of employees. The subject of this research is the management of Hotel Santika Premiere Padang and their staff. This study aims to determine what kind of public speaking and communication styles occur and whether public speaking and leadership communication styles trigger employee motivation.